2017
DOI: 10.4103/jispcd.jispcd_339_17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health education program based on health belief model on oral health behaviors in pregnant women of Fasa city, Fars province, south of Iran

Abstract: Aims and Objectives:Pregnant women are at risk of dental caries and periodontal disease. The purpose of this study was to assess the effectiveness of health education program based on health belief model (HBM) on oral and dental hygiene behaviors in pregnant women in Fasa city.Materials and Methods:This is a clinical trial study carried out on 110 pregnant women selected using random sampling method from health centers in Fasa city in 2016 (55 patients in the experimental group and 55 individuals in control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
11
18
0
1
Order By: Relevance
“…Therefore, motivation and dentistry services with appropriate expenses are required for diabetic patients to perform the recommended oral hygiene-related behaviors correctly and continuously. The results of this study were compatible with those of the studies by Khani Jeihouni et al investigating Health Belief Model constructs and tooth decay index in pregnant women [32], Friel et al investigating the effect of oral hygiene intervention among teenagers in Ireland [33], and Shabibi et al investigating the application of Health Belief Model to diabetic patients self-care [17].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, motivation and dentistry services with appropriate expenses are required for diabetic patients to perform the recommended oral hygiene-related behaviors correctly and continuously. The results of this study were compatible with those of the studies by Khani Jeihouni et al investigating Health Belief Model constructs and tooth decay index in pregnant women [32], Friel et al investigating the effect of oral hygiene intervention among teenagers in Ireland [33], and Shabibi et al investigating the application of Health Belief Model to diabetic patients self-care [17].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, motivation and dentistry services with appropriate expenses are required for diabetes patients to perform the recommended oral hygiene-related behaviors correctly and continuously. The results of this study were compatible with those of the studies by Khani Jeihouni et al investigating the health belief model constructs and tooth decay index in pregnant women [32], by Friel et al evaluating the effect of oral hygiene intervention among teenagers in Ireland [33] and by Shabibi et al investigating the application of health belief model to diabetes patients self-care [17].…”
Section: Discussionsupporting
confidence: 90%
“…This improvement of the present study could be attributed to increase in the knowledge regarding ill effects of not maintaining oral hygiene that was provided to them in educational intervention. The study by Jeihooni et al 14 also confirmed the above-mentioned results favoring the health promotion through HBM model. It is evident from our study result that there is significant increase in the mean score of perceived benefits after intervention.…”
Section: Discussionmentioning
confidence: 55%